OCCURRENCES OF WHEAT CURL MITE ACERIA TOSICHELLA KEIFER 1969 (ERIOPHYIDAE) AND THE ASSOCIATED VIRUSES, (WSMV, HPWMoV, TriMV) IN IRAQ - L. K. Khalaf,; M. Adhab,; L. M. Aguirre-Rojas,; A. E. Timm, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigate the significant wheat yield losses in northern and central Iraq. The cause of these losses was examining the presence of wheat curl mite Aceria tosichella and three viruses vectored by this species – Wheat streak mosaic virus (WSMV), High Plains wheat mosaic virus (HPWMoV), and Triticum mosaic virus (TriMV). Mite specimens were collected from Erbil, Mosul, and Baghdad over three years (2020-2022) and identified using morphological characterization and DNA sequencing of the ITS region. Virus presence was determined using Double Antibody Sandwich-Enzyme-Linked Immunosorbent Assay (DAS-ELISA). Mites were identified conclusively as A. tosichella, providing the first record of this species in Iraq. All three viruses were found to be present, with WSMV having the largest presence as it was detected in 99.56%, then HPWMoV (79.5%) of mite colonies. This is the first record of HPWMoV anywhere in Eurasia besides Ukraine and its widespread presence in Iraq in all three sampled provinces. TriMV was detected only in Erbil. To date this virus has been recorded only in North America and its limited presence in Iraq. The confirmed presence of A. tosichella and three vectored-viruses in Iraq are all new records and critical information for reducing wheat yield losses in this country.